Twinkie, deconstructed : my journey to discover how the ingredients found in processed foods are grown, mined (yes, mined), and manipulated into what America eats - Ettlinger, Steve (Hudson Street Press, 2007)
Like most Americans, Steve Ettlinger eats processed foods. And, like most consumers, he often reads the ingredients label-without a clue as to what most of it means. So when his young daughter asked, ʺDaddy, whatʼs polysorbate 60?ʺ he was at a loss-and determined to find out. From the phosphate mines in Idaho to the corn fields in Iowa, from gypsum mines in Oklahoma to the vanilla harvest in Madagascar, Twinkie, Deconstructed is a fascinating, thoroughly researched romp of a narrative that demystifies some of the most common processed food ingredients-where they come from, how they are made, how they are used-and why. Beginning at the source (hint: theyʼre often more closely linked to rock and petroleum than any of the four food groups), we follow each Twinkie ingredient through the process of being crushed, baked, fermented, refined, and/or reacted into a totally unrecognizable goo or powder with a strange name-all for the sake of creating a simple snack cake. An insightful exploration into the food industry, if youʼve ever wondered what youʼre eating when you consume foods containing mono- and diglycerides or calcium sulfate (the latter, a food-grade equivalent) this book is for you. Book jacket.